Determinants of lower back pain amongst general workers in Universiti Utara Malaysia (UUM) - Samuel Pereira, Adrian (2020)
Rising incident of lower back pain among general workers is a concern in Malaysian workforce. The purpose of this research is to investigate the influence of body postures, workplace design and jobs demand to lower back pain amongst general workers populations in University Utara Malaysia (UUM). This study was conducted by using questionnaire for back pain and Dutch Musculoskeletal questionnaire. The findings of body postures, workplace design and jobs demand in UUM general workers was found to play the greatest role in influencing to lower back pain. This study definitively answers the question regarding correlation between the three main dominant factors that contributing to lower back pain and significant regression on workplace design. Further studies are needed to establish causal relationship and develop preventive measures.